THE EFFECT OF LEARNING STYLE ON STUDENT ACADEMIC ACHIEVEMENT AT PTKIN IN SOUTH SULAWESI - Ismail, Wahyuni; Ikbal, Muhammad; Permata, Srianti (Al Asma: Journal of Islamic Education, 2025)
This study aimed to investigate the effect of learning style (visual, auditory, kinesthetic) on the academic achievement of students at four Islamic State Institutions in South Sulawesi: Alauddin Makassar Islamic State University, Pare-pare Islamic State Institute, Palopo Islamic State Institute, and Watampone Islamic State Institute. Employing an ex post facto quantitative research design, a stratified random sample of 382 students was selected for the study. Data on learning styles were collected using a validated scale based on DePorter & Hernacky's theory. Data analysis used non-parametric statistics of the Kruskal-Wallis type. Descriptive and inferential statistical analyses examined the relationship between learning style and academic achievement. Results indicated that while visual learning styles with a sig value of 0.685 and kinesthetic learning styles with a sig value of 0.544 were not significantly correlated with academic performance (p > 0.05), auditory learning style was found to be a significant predictor of student success with a sig value of 0.047 (p < 0.05). Based on these findings, it is recommended that lecture-based methods, which cater to auditory learners, be prioritized in instructional strategies to enhance academic outcomes for students at these institutions.